Short-term effectiveness of COVID-19 vaccines in immunocompromised patients: A systematic literature review and meta-analysis. Issue 3 (March 2022) - Marra, Alexandre R.; Kobayashi, Takaaki; Suzuki, Hiroyuki; Alsuhaibani, Mohammed; Tofaneto, Bruna Marques; Bariani, Luigi Makowski; Auler, Mariana de Amorim; Salinas, Jorge L.; Edmond, Michael B.; Doll, Michelle; Kutner, José Mauro; Pinho, João Renato Rebello; et al.
Highlights: We performed a systematic review and meta-analysis of 33 observational studies. All COVID-19 vaccine studies compared immunocompromised patients vs. control group. Outcome suggests the effectiveness of COVID-19 mRNA vaccines. Serological response was significantly high in the control group. Summary: Objectives: We aimed to assess the short-term effectiveness of COVID-19 vaccines among immunocompromised patients to prevent laboratory-confirmed symptomatic COVID-19 infection. Methods: Systematic review and meta-analysis. We calculated the pooled diagnostic odds ratio [DOR] (95% CI) for COVID-19 infection between immunocompromised patients and healthy people or those with stable chronic medical conditions. VE was estimated as 100% x (1-DOR). We also investigated the rates of developing anti-SARS-CoV-2 spike protein IgG between the 2 groups. Results: Twenty studies evaluating COVID-19 vaccine response, and four studies evaluating VE were included in the meta-analysis. The pooled DOR for symptomatic COVID-19 infection in immunocompromised patients was 0.296 (95% CI: 0.108–0.811) with an estimated VE of 70.4% (95% CI: 18.9%- 89.2%). When stratified by diagnosis, IgG antibody levels were much higher in the control group compared to immunocompromised patients with solid organ transplant (pOR 232.3; 95% Cl: 66.98–806.03), malignant diseases (pOR 42.0, 95% Cl: 11.68–151.03), and inflammatory rheumatic diseases (pOR 19.06; 95% Cl: 5.00–72.62). Conclusions: We found COVID-19 mRNA vaccines were effective against symptomatic COVID-19 among the immunocompromised patients but had lower VE compared to the controls. Further research is needed to understand the discordance between antibody production and protection against symptomatic COVID-19 infection. Graphical abstract: Image, graphical abstract